Analisis Kinerja Ekspor Nonmigas Jawa Timur dengan Pendekatan Regresi Kuantil Smoothing Splines Periode 2012-2021 - Rinda Fitriani; Husnul Chotimah (Seminar Nasional Official Statistics, 2022)
East Java's industrialization is predicted to increase in line with the region's strategic role. The Export-Led Industrialization (ELI) strategy in East Java has been actively implemented since 1995. The export value of East Java is dominated by non-oil and gas exports. However, the development of East Java's non-oil and gas exports tends to fluctuate. It is unstable, so optimal export performance is needed to succeed in the ELI strategy's industrialization. This study analyses the competitiveness and performance of East Java's non-oil and gas exports by involving the inflation variable. Quantile regression modelling of smoothing splines was used in this study. The results of the analysis show that the inflation rate has a negative effect on East Java's non-oil and gas exports. The best performance of East Java's non-oil and gas exports is when the export value in a certain period is above the 0.5 and 0.75 quintiles (high and very high categories).